Effects of bio-oil - diesel blends: the performance and emissions of diesel engines with intake manifold variations - Farid Majedi; Agus Choirul Arifin; Alfi Tranggono Agus Salim; Agus Ma’ruf Prasetya (Universitas Mercu Buana, 2022)
Alternative fuels such as vegetable oil, biodiesel, and bio-oil are potential alternatives for diesel engines. Bio-oil is one of the products of the decomposition process of chemical and organic matter by adding heating process without oxygen is called rapid pyrolysis. Bio-oil in the pyrolysis process is made from Brem waste. Brem is a typical food from the district of Madiun, Indonesia. This research is important because the switch from petroleum-sourced fuel to Bio-Oil oil cannot be automatically applied to diesel engines. Spray quality and combustion process, type and quality of fuel, and engine design and condition are some of the important parameters affecting diesel engine performance. Research data is very important because it can determine the intake manifold and the best bio-oil-diesel blends to be used in the operation of diesel engines with bio-oil-diesel blends. The research uses three variations of the intake manifold form. Variations of research with lamp loading of 650, 1300, 1950 and 2600 watts determine specific power and fuel consumption. Use an opacity smoke meter to determine the opacity of diesel engine exhaust gases. The fuel used is pure diesel fuel and Bio-Oil fuel B10, B15, and B20 resulting from the pyrolysis of Brem waste with a fuel volume of 25 ml for each research variable. The results of testing the intake manifold variation and the bio-oil-diesel blended are the intake manifold variation 1 with a fuel mixture variation of 20 % Bio-Oil - 80% pure diesel (B20), which has the best results both electric power, speciﬁc fuel consumption and opacity.